2012
DOI: 10.1016/j.ijscr.2012.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Phytobezoar in Meckel's diverticulum: A rare cause of small bowel obstruction

Abstract: The conventional x rays studies were inconclusive whereas abdominal contrast enhanced CT led to a definitive diagnosis. Explorative laparotomy or laparoscopy is mandatory in these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The mass could be outlined by the bowel wall and present characteristic internal gas bubbles. CT scan is useful to localize the bezoar as well as to identify complications like perforation and obstruction [10].…”
Section: Discussionmentioning
confidence: 99%
“…The mass could be outlined by the bowel wall and present characteristic internal gas bubbles. CT scan is useful to localize the bezoar as well as to identify complications like perforation and obstruction [10].…”
Section: Discussionmentioning
confidence: 99%
“…Bini et al reports a rare case of phytobezoar in a meckels diverticulum causing bowel obstruction. [11] The management of Meckels diverticulum presents substantial debate till date. In an extensive study at Mayo Clinic, Park et al advocated the removal of incidentally found asymptomatic Meckels diverticulum in male sex, less than 50 years age group or which is more than 2cm long, especially if having histologically abnormal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…It is found in about 2% of the population. However, it rarely gives rise to symptoms and its discovery is usually accidental [11]. …”
Section: Discussionmentioning
confidence: 99%